2008
DOI: 10.1108/10610420810904149
|View full text |Cite
|
Sign up to set email alerts
|

Online satisfaction, trust and loyalty, and the impact of the offline parent brand

Abstract: Purpose -The objective of this paper is to examine online brand relationships, and the linkage between satisfaction, trust, and loyalty on the web site level. The web site is considered to be an extension of the parent brand. It also seeks to explore the effects of offline experiences on web site-level experiences. Design/methodology/approach -Hierarchical regression analysis is applied in order to test the hypotheses. The data are based on an online survey (n ¼ 867) conducted on a Finnish consumer-magazine we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
107
0
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(128 citation statements)
references
References 43 publications
(59 reference statements)
9
107
0
12
Order By: Relevance
“…Prior study was also found that the higher the level of e-satisfaction, the higher the level of e-loyalty (Anderson & Srinivasan, 2003;Luarn & Lin, 2003), in other words, that e-loyalty was significantly influenced by e-satisfaction Research done by Kassim & Salaheldin (2009) found that both e-Satisfaction and e-Trust significantly affected e-Loyalty, however the relationship between e-Satisfaction and e-Trust was not significant. To the contrary, another empirical investigation found the existence of a relationship between e-Satisfaction and e-Trust (Horppu, et al, 2008;C. Kim, et al, 2008).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior study was also found that the higher the level of e-satisfaction, the higher the level of e-loyalty (Anderson & Srinivasan, 2003;Luarn & Lin, 2003), in other words, that e-loyalty was significantly influenced by e-satisfaction Research done by Kassim & Salaheldin (2009) found that both e-Satisfaction and e-Trust significantly affected e-Loyalty, however the relationship between e-Satisfaction and e-Trust was not significant. To the contrary, another empirical investigation found the existence of a relationship between e-Satisfaction and e-Trust (Horppu, et al, 2008;C. Kim, et al, 2008).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…E-service quality dimensions also had significant relationship to e-trust (Floh & Treiblmaier, 2006;Horppu, Kuivalainen, Tarkianinen, & Ellonen, 2008) and e-service quality as represented by web site quality also had a significant and positive impact on e-trust (Chang & Chen, 2008). Some studies have found that e-loyalty was significantly influenced by e-service quality and Parasuraman et al, (2005) have identified relationships between each of the e-service quality determinants and eloyalty.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…From the customer's viewpoint, it has created new and possibly less costly ways of participating in commercial activities [182]. From the business perspective, market globalization, along with the decreasing effectiveness of offline marketing, has motivated organizations to shift their plans to include Internet marketing [120]. Hence, consumers have increasingly favoured online shopping [166], gradually leading more Business-to-Customer (B2C) companies to establish an Internet presence in an effort to attract new and maintain existing customers for long-term profitability [203].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, creating customer loyalty and satisfaction is the major objective for online companies to increase profitability and obtain and maintain competitive advantage. To do so, companies need to develop a thorough understanding of the antecedents of loyalty on the World Wide Web [120]. Shankar et al [181, p. 154] note that -firms need to gain a better understanding of the relationship between satisfaction and loyalty in the online environment to allocate their online marketing efforts between satisfaction initiatives and loyalty programs‖.…”
Section: Introductionmentioning
confidence: 99%